V. N. Beneshevich and E. Schwartz: The Experience of International Cooperation and Scientific Friendship - Priest Maksim V. Sorokin (Вестник Екатеринбургской духовной семинарии, 2022)
The relationship between Vladimir Nikolaevich Beneshevich and the German historian and philologist Eduard Schwartz lasted for 25 years, starting from the international recognition of the Russian scientist and until his tragic death. E. Schwartz became an intermediary in many scientific projects for the Russian scientist. The matter of a lifetime of V. N. Beneshevich — publication of a corpus of texts of Byzantine law — was difficult to implement in post-revolutionary Russia, while in Germany it found support in the person of E. Schwartz. Repressions against V. N. Beneshevich interrupted him to carry out his scientific plans in full measure. As soon as the political situation in Germany changed in 1933, active scientific contacts of Beneshevich with the German scientist were labeled by Soviet authorities as espionage. The publication of the Synagogue of John Scholastikos in 1937 in Nazi Germany ultimately initiated the persecution of V. N. Beneshevich for political reasons, and he was shot in 1938. V. N. Beneshevich received world fame and universal recognition thanks to the assistance of E. Schwartz, but at the same time their cooperation became fatal for V. N. Beneshevich. The article reconstructs history of the long-term communication and cooperation of the two scientists. Previously unpublished correspondence, mainly the letters of V. N. Beneshevich from the E. Schwartz archive in Munich, introduced into scientific circulation for the first time, has supplemented numerous previous studies on the life and work of the Russian historian and canonist and become an important source of the history of the relationship between the scientists.